ANALISIS PERILAKU KONSUMEN TERHADAP PRODUK BERMEREK DI KALANGAN MASYARAKAT KABANJAHE: Studi Kasus Masyarakat Jalan Mesjid, Kelurahan Lau Cimba, Kabanjahe - Nurbeti Nurbeti (Universitas Methodist Indonesia, 2019)
Consumers are an important element in consumer behavior, where a product opportunity in the market must be analyzed, studied, and understood how consumers view behavior. The purpose of this study is to find out the influence of consumer behavior on cultural, social, personal, and motivational indicators of branded products. This study used 89 samples at Jalan Mesjid Kelurahan Lau Cimba, Kabanjahe. The data analysis technique uses multiple linear regression analysis. The results showed that culture, social, personal, and motivation had a positive and significant effect of 66,2%. The result of the study also shows a simultaneous test where F count 41,222 > F table 2,53, meaning that the four variables have an influence. Thus the analysis of consumer behavior towards branded products is acceptable.